Big Steel, Invention, and Innovation - Adams, Walter; Dirlam, Joel B. (Quarterly Journal of Economics, 1966)
Introduction: the “Schumpeterian” hypothesis, 167. — I. Oxygen steelmaking: the history of its invention and innovation, 169. — II. Some cost and profit implications of innovative lethargy, 184. — III. Conclusion, 188.